A One-Year Follow-Up of Two Ahmed Glaucoma Valve Models (S2 and FP7) for Refractory Glaucoma: A Prospective Randomized Trial - Elbaklish KH (Dove Medical Press, 2020)
Khaled Hamdi Elbaklish, Wael Adel Gomaa Ophthalmology Department, Ain Shams University, Cairo, EgyptCorrespondence: Khaled Hamdi ElbaklishOphthalmology Department, Ain Shams University, Abbasi, Cairo, EgyptTel +20 100 005 7550Email khaled.hamdy62@yahoo.comAim: To compare a range of clinical outcome variables (intraocular pressure, glaucoma medications, visual acuity, and complications) between two Ahmed glaucoma valve (AGV) models (S2 and FP7).Methods: This was a prospective and randomized clinical trial. Fifty-six patients with refractory glaucoma were randomly assigned to be implanted with either a polypropylene (S2) or silicone (FP7) Ahmed glaucoma valve. The primary outcome measure was a surgical success, defined as an IOP ≤ 16 mm Hg (without medication), and guarded success, defined as a controlled IOP ≤ 16 mmHg (with medication). Failure was defined as when the IOP lay outside of the successful range on two consecutive visits (> 16 mmHg, despite medication).Results: Mean follow-up period was 398.42 ± 12.34 days (range, 380– 420 days) for the S2 group and 401.75 ± 9.78 days (range, 385– 420 days) for the FP7 group; these values were not significantly different (P = 0.27). After 12 months of follow-up, the baseline IOP (45.42 mmHg) fell significantly to 16.14 mmHg in the S2 group (p <  0.000); there was also a significant reduction in IOP in the FP7 group (from 44.17 mmHg to 15.18 mmHg in FP7 group, p < 0.000). At the last follow-up examination, the mean IOP in the S2 group was 16.14 ± 3.18 mmHg, while that of the FP7 group was 15.18 ± 2.75 mmHg; there was no significant difference between the two groups with this respect (p = 0.23). The mean number of medications used by patients in the S2 and FP7 groups was 2.92 ± 1.27 and 2.75 ± 1.43, respectively; there was no significant difference between the two groups with this respect (p = 0.32). There was no significant difference between the FP7 and S2 groups with regard to their relative success rate (17.89% [5/28] versus 10.7% [3/28], respectively; p = 0.38).Conclusion: Our data show that the S2 and FP7 models of AGV were both effective in lowering IOP and reducing the need for glaucoma medications. Although these two AGV models had similar dimensions, they were constructed from different materials. However, there were no significant clinical differences between the S2 and FP7 AGV groups after 12 months of follow-up. Furthermore, our data indicate that bleb encapsulation was the primary factor responsible for failure rate and the need for glaucoma medication in both the S2 and FP7 groups. Our analysis further indicates that the S2 and FP7 Ahmed valves are associated with a high risk of failure when considered as a first-line therapy for cases experiencing trabeculectomy.Clinical Trial Registration: NCT04214847.Keywords: Ahmed glaucoma valve, S2, FP7, IOP, encapsulation